The Night Eating Questionnaire through the lens of the Rasch model - Vojkan Aleksic; Marija Milic; Jelena Dotlic; Biljana Jeremic; Branislav Djerkovic; Ivan Radic; Ana Odalovic; Ljiljana Kulic; Milivoje Galjak; Tatjana Gazibara (Heliyon, 2024)
Previous research focused on the conventional approaches to test psychometric characteristics of the Night Eating Questionnaire (NEQ). The purpose of this research was to examine the psychometric properties of the Night Eating Questionnaire using the Rasch model in a sample of university students. The study was carried out from November 2018 to March 2019 on 300 students in health sciences at the University of Pristina temporarily seated in Kosovska Mitrovica, who completed the NEQ. A confirmatory factor analysis (CFA) suggested that the Serbian version mirrored the original NEQ structure: Goodness of fit index = 0.978, Comparative fit index = 0.996, Tucker-Lewis index = 0.995, Root Mean Square Error of Approximation = 0.011 and Standardized Root Mean Square Residual = 0.057. The Cronbach's alpha coefficient for the total scale was 0.627. The Rasch analysis showed that the item separation index classified the items into six groups based on their level of difficulty. The person reliability index separated well night eaters from day eaters. Few items did not fit the adequate range for the infit/outfit statistics. Overall, there were several groups of NEQ items that have a distinctive difficulty level, but the difference was not a remarkable one. This means that most students did not have night eating syndrome (NES), despite various levels of item difficulty. The NEQ performs well in the efforts to distinguish people who eat and do not eat at night. Most students reported conventional eating patterns and only a few had NES. The properties of the NEQ warrant its use in further night eating research.